Factor analysis of implementation of Antenatal Care (ANC) service standards by midwivesat the banda raya health center Banda Aceh City - Muna, Sirajul; Kurniawati, Evi; Aryani, Roza (Institute Of Computer Science (IOCS), 2024)
The maternal mortality rate in Banda Aceh City from 2014-2018 experienced fluctuation when in 2014 there were 5 deaths, in 2015 there were 6 deaths, in 2016 there were 2 deaths, in 2017 there were 2 deaths and in 2018 there were 3 maternal deaths. The aim of the research is to investigate The Implementation Factors of Antenatal Care (ANC) Service Standard done by midwives at the Banda Raya Community Health Center, Banda Aceh City. The research method used is descriptive analytic with a cross-sectional study design. There were 30 population of midwives which were selected by a sampling technique, namely non-probability sampling. Analysis of this data used the Chi Square statistical test with computerized assistance. The significance value (p) was 0.05 with a confidence value of 0.95. The research results showed variables which were related to the implementation of ANC 10 T were midwife knowledge (p 0.046), length of service (p 0.011) and Midwife training Update (p 0.019), while unrelated variable was midwife education (p 0.411). The Conclusion of this research is that there is a relationship between midwives' knowledge, length of service and Midwefery training Update with the implementation of ANC 10 T in the Banda Raya Community Health Center working area and there is no relationship between midwife education and the implementation of ANC 10 T in the Banda Raya Community Health Center work area. Thus, Midwives are expected to increase their knowledge and skills regarding ANC standards through training or further education.